Deep space observations of conditionally averaged global reflectance patterns - Kostinski, Alexander; Marshak, Alexander; Várnai, Tamás (Frontiers in Remote Sensing, 2024)
Deep space climate observatory (DSCOVR) spacecraft drifts about the Lagrangian point ≈ 1.4-1.6 × 10 6 km from Earth, where its Earth polychromatic imaging camera (EPIC) observes the entire sunlit face of the Earth every 1 to 2 hours. In an attempt to detect "signals", i.e., longer term changes and semi-permanent features such as the ever-present ocean glitter while suppressing geographic "noise", here we introduce temporally and conditionally averaged reflectance images, performed on a fixed grid of pixels and uniquely suited to the DSCOVR/EPIC observational circumstances. The resulting images (maps), averaged in time over months and conditioned on surface/cover type such as land, ocean, or clouds, show seasonal dependence literally at a glance, e.g., by an apparent extent of polar caps. Clear ocean-only aggregate maps feature central patches of ocean glitter, linking directly to surface roughness and, thereby, global winds. When combined with clouds, these blue planet "moving average" maps also serve as diagnostic tools for cloud retrieval algorithms. Land-only images convey the prominence of Earth' deserts and the variable opacity of the atmosphere at different wavelengths. Insights into climate science, diagnostic as well as educational tools are likely to emerge from such average reflectance maps.